2018
DOI: 10.1111/jcpe.12898
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of 30,959 implants: Risk factors associated with early and late implant loss

Abstract: General factors such as male sex, elderly patients, mandibular anterior location, bone augmentation and short implants were associated with implant loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
136
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(163 citation statements)
references
References 45 publications
11
136
2
3
Order By: Relevance
“…Due to the own traits of each case in clinical work of implantology, it was considered that a multifactorial etiology would lead to implant loss . As for participant variables, including gender and age, a higher failure risk was discovered in males than in females, which was in accordance with previous findings . In contrary, no significant difference of survival rates was detected between groups classified with age in our study, suggesting that age was not able to be a latent risk factor for implant loss.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Due to the own traits of each case in clinical work of implantology, it was considered that a multifactorial etiology would lead to implant loss . As for participant variables, including gender and age, a higher failure risk was discovered in males than in females, which was in accordance with previous findings . In contrary, no significant difference of survival rates was detected between groups classified with age in our study, suggesting that age was not able to be a latent risk factor for implant loss.…”
Section: Discussionsupporting
confidence: 90%
“…Different factors related to implant loss were explored, such as age, sex, implant length and diameter, expansion technique, implant location and so on . The conclusions were diverse in the analyses of different populations.…”
Section: Introductionmentioning
confidence: 99%
“…The literature supports the evidence that SNPs play an important role in the transcription of these inflammatory mediators and may influence the osseointegration success, including single‐nucleotide polymorphism (SNPs) in MMPs …”
Section: Discussionmentioning
confidence: 57%
“…In this study, we observed a number of volunteers with reliable estimated statistical power, despite put out smokers—smoking is a strong risk factor for early implant failure . In addition, others risk factors with age, status periodontal, medically compromised, and position implant were exclude or matched.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation